American GI Forum 1993 - San Jose Queen Coronation - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the Thirty-Third Annual Flores Mexicanas Queen Coronation Ball, presented by the San Jose Chapter of the American GI Forum.